Perceived social support on objective measured sedentary behavior of stroke patients: the mediating role of exercise self-efficacy - Wei, Jianing; Yang, Fanjiayi; Dong, Xiaofang (Frontiers in Psychology, 2024)
Introduction As stroke patients may have impaired motor function, there may have increased sedentary behavior. Factors associated with sedentary behavior need to be explored to develop targeted interventions. Although studies explore the effects of exercise self-efficacy and perceived social support on sedentary behavior, the relationship is not clear. The aim of this study was to explore the mediating effect of exercise self-efficacy on perceived social support and objective measured sedentary behavior in stroke patients. Methods The random sampling method was adopted to select 275 stroke patients from the neurology department of a third-grade hospital of Henan Province from June 2023 to March 2024 in a cross-sectional descriptive study. A general data questionnaire, exercise self-efficacy scale, perceived social support scale, and ActiGraph GT3X accelerometer were used to investigate. The structural equation model was used to analyze the mediating effect of exercise self-efficacy between perceived social support and sedentary behavior. Results The mean sedentary behavior time in stroke patients in this study was (479.65 ± 112.65) min, the mean score of perceived social support was (47.53 ± 17.16), and the mean score of exercise self-efficacy was (24.19 ± 6.25). The correlation analysis revealed that, the sedentary behavior of stroke patients was negatively correlated with exercise self-efficacy and perceived social support. The results of the mediation analysis showed that exercise self-efficacy played a partial mediating role between perceived social support and sedentary behavior. Conclusion Perceived social support and exercise self-efficacy were influential factors in sedentary behavior. Moreover, the impact of perceived social support on sedentary behavior was partially mediated by exercise self-efficacy. Therefore, to decrease the sedentary behavior, it is crucial to improve the level of perceived social support in stroke patients. Patients with less perceived social support can improve their exercise self-efficacy and thus perceive more social support.